Sovereign Investor Relations : From Principles to Practice - Knight, James (IMF Working Papers; Working Paper, 2020)
This paper defines sovereign investor relations (IR) and places it in the context of modern debt management theory. It highlights the role that improvements in IR and debt transparency can play in improving the cost-risk tradeoff in debt management, supporting market access and acting as a first line of defense in times of crisis. It sets out a policy framework and institutional arrangements for effective IR, as well as discussing the various practices, publications and strategies that underpin an IR program.